Unpacking Muslim Scholars’ Political Apathy in Northern Nigeria: Beyond the Pulpit to Political Engagement - Saleh Hassan; Muhammad Jungudo, Ahmad; Muhammad Babayya, Abubakar (Journal of Political Islam, 2025)
Abstract Muslim scholars have historically been recognised as key figures in stabilising both the spiritual and political spheres in Northern Nigeria. Despite these roles, they have increasingly shown a decline in active engagement, creating space for incompetent or self-serving individuals to dominate governance. Sectarian divisions, lack of political literacy, financial limitations, and negative perceptions of politics as a ‘dirty’ game all worsen political apathy. This study argues that the withdrawal of Muslim scholars from political engagement, such as contesting, contradicts the theological and historical foundations of Islam, which emphasise leadership, public welfare, and justice. Consequently, this apathy diminishes scholars’ moral authority and hinders Muslim communities from influencing governance positively. The study aims to highlight the necessity of redefining scholars’ roles beyond the pulpit to include active involvement in governance. A descriptive approach within the qualitative method was employed, relying largely on secondary sources and personal interviews with Muslim scholars and politicians in Northern Nigeria. This triangulation fosters a comprehensive understanding of the challenges and impacts of political apathy among scholars. The findings indicate that factors such as godfatherism, greed among scholars, misconceptions among the public, and sectarian divisions contribute to this apathy. It also reveals that, whereas Christian clerics actively contest elections, Muslim scholars largely abstain, leading to a leadership vacuum. This results in a decline in public trust. Therefore, by engaging in politics with integrity, Muslim scholars can restore public confidence and exemplify leadership based on Islamic principles of justice and accountability.